1998
DOI: 10.1530/jrf.0.1140307
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of cytokeratins and vimentin by highly invasive trophoblast in the white-winged vampire bat, Diaemus youngi, and the black mastiff bat, Molossus ater, with observations on intermediate filament proteins in the decidua and intraplacental trophoblast

Abstract: Histological and immunocytochemical studies of gravid reproductive tracts obtained from the white-winged vampire bat (Diaemus youngi) and the black mastiff bat (Molossus ater) have established that both species develop unusually invasive trophoblast. This is released by the developing discoidal haemochorial placenta, expresses both cytokeratins and vimentin, and invades the myometrium and adjacent tissues (including the ovaries) via interstitial migration within the walls of maternal blood vessels. Hence, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Up-regulated vimentin expression was shown to be associated with invasive cells during the development and growth of the placenta [Walter and Schonkypl, 2006]. EMT has also been described in maternal invasion of the intermediate trophoblasts in humans [Haigh et al, 1999] and bats [Badwaik et al, 1998]. …”
Section: Vimentin In Normal Development and Normal Tissuesmentioning
confidence: 99%
“…Up-regulated vimentin expression was shown to be associated with invasive cells during the development and growth of the placenta [Walter and Schonkypl, 2006]. EMT has also been described in maternal invasion of the intermediate trophoblasts in humans [Haigh et al, 1999] and bats [Badwaik et al, 1998]. …”
Section: Vimentin In Normal Development and Normal Tissuesmentioning
confidence: 99%
“…that existing on the island of Trinidad) (Rasweiler, 1988;Badwaik et al, 1998) opens the door to much more probing studies of significant reproductive, developmental and evolutionary problems. It provides a means of more accurately characterizing synchronized or seasonal breeding patterns in the wild.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence indicates that the Trinidadian population of M. rufus that provided breeding stock for this study is reproductively synchronized, and that some of the females may carry two pregnancies per year in quick succession (Rasweiler, 1988;Badwaik et al, 1998). The reproductive biology of M. rufus has also been extensively studied under controlled conditions in captivity (Rasweiler, 1987(Rasweiler, , 1988(Rasweiler, , 1990a(Rasweiler, ,b, 1991a(Rasweiler, ,b, 1992(Rasweiler, , 1993Badwaik et al, 1998), revealing this species to be an interesting model for studies of the biology of menstruation, trophoblastic growth and differentiation, and placental morphogenesis.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Molossus ater delays development of an invasive placenta until late in gestation. Following implantation, initial development of a diffuse, endotheliochorial placenta results in only superficial penetration of the uterine endometrium until it is replaced by the development of a more invasive, hemochorial placenta relatively late in gestation (Badwaik et al, 1998;Rasweiler, 1992). Based on comparisons of reproductive strategies in bats, Rasweiler has suggested that menstruation in each of the two bat families may have evolved separately from a nonmenstruating ancestor (Raisweiler, 1991b;Rasweiler and de Bonilla, 1992).…”
Section: Dynamics Of Trophoblastic Activity During Placentationmentioning
confidence: 99%